Echinococcus multilocularis infection of the liver presenting as abdominal wall fistula. (15th April 2014) - Juodeikis, Zygimantas; Poskus, Tomas; Seinin, Dmitrij; Strupas, Kestutis
Abstract : Echinococcus multilocularis causes infection where the most commonly affected organ is the liver, followed by the lung, kidney, bone and the brain. Other sites such as the heart, spleen, pancreas and soft tissues are very rarely affected. Surgical treatment combined with chemotherapy using various technical approaches remains the main therapeutic modality for echinococcal liver disease. To the best of our knowledge there are less than five clinical cases of cutaneous presentation of liver alveolar echinococcosis described. We present a unique case of liver echinococcosis presenting as recurrent abdominal wall fistula and abscess in a 29-year-old man. Diagnosis was based on CT imaging, serological analysis and histological findings from the fistula. Medical treatment with albendazole was initiated and liver resection was performed. The patient has no symptoms and signs of recurrence 1 year after operation, while still on albendazole therapy. This case description highlights the importance of early suspicion and treatment of unusual echinococcosis clinical presentations.